Derivation of algal acute to chronic ratios for use in chemical toxicity extrapolations. (January 2021) - Brill, Jessica L.; Belanger, Scott E.; Barron, Mace G.; Beasley, Amy; Connors, Kristin A.; Embry, Michelle; Carr, Greg J.
Abstract: Algal toxicity studies are required by regulatory agencies for a variety of purposes including classification and labeling and environmental risk assessment of chemicals. Algae are also frequently the most sensitive taxonomic group tested. Acute to chronic ratios (ACRs) have been challenging to derive for algal species because of the complexities of the underlying experimental data including: a lack of universally agreed upon algal inhibition endpoints; evolution of experimental designs over time and by different standardization authorities; and differing statistical approaches (e.g., regression versus hypothesis-based effect concentrations). Experimental data for developing globally accepted algal ACRs have been limited because of data availability, and in most regulatory frameworks an ACR of 10 is used regardless of species, chemical type or mode of action. Acute and chronic toxicity (inhibition) data on 17 algal species and 442 chemicals were compiled from the EnviroTox database (https://envirotoxdatabase.org/ ) and a proprietary database of algal toxicity records. Information was probed for growth rate, yield, and final cell density endpoints focusing primarily on studies of 72 and 96 h duration. Comparisons of acute and chronic data based on either single (e.g., growth rate) and multiple (e.g., growth rate, final cell density) endpoints were used to assess acute and chronic relationships. Linear regressions of various model permutations were used to compute ACRs for multiple combinations of taxa, chemicals, and endpoints, and showed that ACRs for algae were consistently around 4 (ranging from 2.43 to 5.62). An ACR of 4 for algal toxicity is proposed as an alternative to a default value of 10, and recommendations for consideration and additional research and development are provided. Graphical abstract: Image 1 Highlights: Algae are often the most sensitive taxonomic group in environmental risk assessments. Application of acute to chronic ratios (ACRs) are often used to estimate chronic toxicity values. An ACR of 10 is commonly used for all test species (algae, invertebrates and fish). A detailed literature review suggests algal inhibition assays do not fit this profile. An ACR of 4 is proposed for algal toxicity as an alternative to a default value of 10.